Pengaruh Green Packaging dan Green Advertising terhadap Purchase Intention Produk Sensatia Botanicals di Indonesia - Irgi Riftian Ghandi; Apriatni Endang Prihatini (Universitas Diponegoro, 2026)
Abstract: The eco-friendly beauty industry in Indonesia is estimated to grow by 5.33% per year in the period 2024–2029 based on Statista Natural Cosmetics data. One of the brands that implements the sustainability concept is Sensatia Botanicals. However, Sensatia Botanicals' sustainability initiative faces several challenges, such as limited access for consumers and the effectiveness of green advertising which is still limited in reaching a wider audience. This study aims to analyze the effect of green packaging and green advertising on the purchase intention of Sensatia Botanicals products in Indonesia. Using explanatory research with a quantitative approach, data was collected through purposive sampling with 144 respondents and analyzed using SPSS 26. The results showed that green packaging and green advertising had a partial or simultaneous effect on the purchase intention of Sensatia Botanicals products in Indonesia. This study recommends that Sensatia Botanicals can improve the effectiveness of its sustainability strategy by clarifying information on environmentally friendly packaging, designing more ergonomic packaging, and communicating energy-efficient production processes. In addition, companies need to use attractive visuals, highlight certifications, clearly convey product features, and add FAQs and more detailed product content. The inclusion of QR codes on packaging is also recommended to provide more comprehensive information to consumers.Abstraksi: Industri kecantikan ramah lingkungan di Indonesia diperkirakan mengalami pertumbuhan sebesar 5,33% per tahun pada periode 2024–2029 berdasarkan data Statista Natural Cosmetics. Salah satu merek yang menerapkan konsep keberlanjutan adalah Sensatia Botanicals. Namun, inisiatif keberlanjutan Sensatia Botanicals menghadapi tantangan, seperti keterbatasan akses bagi konsumen serta efektivitas green advertising yang masih terbatas dalam menjangkau audiens yang lebih luas. Penelitian ini bertujuan untuk menganalisis pengaruh green packaging dan green advertising terhadap purchase intention produk Sensatia Botanicals di Indonesia. Menggunakan explanatory research dengan pendekatan kuantitatif, data dikumpulkan melalui purposive sampling dengan 144 responden dan dianalisis menggunakan SPSS 26. Hasil penelitian menunjukkan bahwa green packaging dan green advertising berpengaruh secara parsial maupun simultan terhadap purchase intention produk Sensatia Botanicals di Indonesia. Penelitian ini merekomendasikan agar Sensatia Botanicals dapat meningkatkan efektivitas strategi keberlanjutannya dengan memperjelas informasi kemasan ramah lingkungan, mendesain kemasan lebih ergonomis, serta mengomunikasikan proses produksi hemat energi. Selain itu, perusahaan perlu menggunakan visual menarik, menonjolkan sertifikasi, menyampaikan fitur produk dengan jelas, serta menambahkan FAQ dan konten produk yang lebih detail. Penyertaan QR code pada kemasan juga disarankan untuk memberikan informasi yang lebih komprehensif kepada konsumen.